ASSESSMENT OF GENETIC DIVERSITY WITHIN GERMPLASM ACCESSIONS IN TOMATO USING MORPHOLOGICAL AND MOLECULAR MARKERS - S. Naz; A. Zafrullah; K. Shahzadhi; N. Munir (Journal of Animal and Plant Sciences, 2013)
A total of 25 high yielding tomato accessions were selected for the characterization that helped in the reliable varietal selection programme for breeding. All tomato accessions were analyzed by two parameters e.g. morphological and molecular parameters. For morphological characterization the plant height, shape, size, leaf length and width, and fruit size, colour and shape were selected and for molecular characterization RAPD markers were used. A total 25 RAPD decamer primers were selected for the genetic analysis of all tomato accessions. Only 15 polymorphic RAPD primers were accessed for the genetic distance calculation to find out the phylogenetic relationship among 25 tomato accessions under study. A total of 130 loci were generated outof which 98 were polymorphic by 15 primers with 05-14 loci/primer having fragment’s size range from 400to 2500bp maximum. The Nie and Lie’s Coefficients was used to calculate the genetic similarity. The extent of genetic diversity and construction of phylogenetic tree was done by DNAMANN software. The average genetic similarity observed across all the genotypes was 75.6% with 24.4% polymorphismin 25 tomato accessions. Although RAPD study supports the morphological characters but not upto 100%.
Keywords: Randomly amplified polymorphic DNA; Polymerase chain reaction; Lycopersiconesculentum